SISTEM INFORMASI DAN PROMOSI PENJUALAN ONLINE PADA ALAMI HERBAL - Sri Muryani (Jurnal Sistem Informasi, 2014)
Abstract— Alami Herbal is a store that sells many kinds fo herbal product with a focus on good service and good quality. The difficulty of delivering information about herbal product, the difficulty of finding a good media campaign , then it encourages Alami Herbal searching for alternative media to promote their products . One way is using online media . With the Internet, information is easily passed from one to another without being obstructed time and distance . The purpose of this research is to produce an information system and promotional web-based, expand the sales area and facilitate the transaction. Consumers who want to buy a product does not necessarily have to come to the store or outlite, because the information submitted through the website can be accessed online anywhere and anytime. Data collection methods used include direct interviews to source the required data . Another method is to collect literature references related to the topic of online sales . This research is expected to be a means of marketing and promotion of effective and efficient products for Alami Herbal for the present and future.